Slow travel : reconnecting with the world at your own pace - Watson, Penny (Hardie Grant Travel, 2019)
A beautifully designed and practical compendium of places, activities, tours and experiences that will inspire you to get on the road in your own time and on your own terms. This book explores slow travel as a physical or philosophical endeavour, taking readers off the beaten track and through nature, and unveils journeys that will nurture talent and ignite the inner-self. In this fast-paced world, it's worth adjusting your vacation time to a pace we can all strive to keep up with.
Keywords: matkailu; ekomatkailu; luontomatkailu; elämysmatkailu; kaupunkimatkailu; kulttuurimatkailu; matkailukohteet